Effect of the growth and yield attributes of sunflower and chickpea with response to different doses and methods of Phosphorus Solubilizing Bacteria in combinationwith different Phosphorus levels: Effect of the growth and yield attributes of sunflower and chickpea with response to different doses and methods of Phosphorus Solubilizing Bacteria in combinationwith different Phosphorus levels - MUDIGIRI CHANDANA; A AZIZ QURESHI; S HARISH KUMAR SHARMA; S TRIVENI (Journal of Oilseeds Research, 2023)
A study was conducted on sunflower and chickpea in sandy loam soils during Rabi 2020 at PJTSAU, Rajendranagar, Hyderabad. This study was focused to know the response of the liquid and powdered PSB on growth and yield attributes of sunflower and chickpea. For this experiment the treatment combination includes, different methods (liquid and powdered) and doses (@ 3 and 6 kg ha-1 for soil application and 50 ml L-1 for drenching) of Phosphorus Solubilizing Bacteria (PSB) along with different phosphorus levels. Phosphorus plays a key role in photosynthesis, metabolism of sugars, energy storage and transfer, cell division, cell enlargement and transfer of genetic information. Inoculation with PSB known to produce the growth hormones like Indole - Acetic Acid and Gibberillic Acid which might favour to increase plant height. The results reported that there was a significant effect of PSB on the plant height, Head diameter, number of pods/plant and non-significant effect on plant stand and test weight. Among, all the treatments the highest plant height (124.33 cm) and head diameter (16.23 cm) at maturity stage in sunflower was seen with 75% P + PSB @ 6 kg/ha and the highest plant height (51.13 cm) and number of pods/plant (26.07) at maturity stage in chickpea was seen with 50% P+ PSB @ 6 kg/ha. There was a non significant effect of PSB on plant stand and test weight. With the application of the PSB there was a reduction of the application of the phosphorus fertilizer to the extent of 25% in sunflower and 50% in chickpea.